2015
DOI: 10.1002/hep.27422
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor mental and physical health status among patients with chronic hepatitis C infection: The Chronic Hepatitis Cohort Study (CHeCS)

Abstract: Aims Our objective was to assess the extent and risk factors for depression and poor physical health among patients with chronic hepatitis C virus (HCV) infection. Methods We surveyed HCV-infected patients seen at four large healthcare systems participating in the Chronic Hepatitis Cohort Study (CHeCS). Survey data included demographics, depression and physical health measures, substance use history, current social support, recent stressor exposures, and, from the electronic medical record, treatment history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 42 publications
4
68
1
2
Order By: Relevance
“…The CHeCS survey was designed to collect data on patient demographics, reported hepatitis risk factors, comorbidities, physical and mental functioning, use of alcohol, drug abuse, and chronic hepatitis treatment history (4). As reported previously, of more than 12,000 patients who met the hepatitis C cohort inclusion criteria, almost 8,000 were known to be alive and not institutionalized and sampled to be surveyed by mail and telephone during 2010–2012 (4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CHeCS survey was designed to collect data on patient demographics, reported hepatitis risk factors, comorbidities, physical and mental functioning, use of alcohol, drug abuse, and chronic hepatitis treatment history (4). As reported previously, of more than 12,000 patients who met the hepatitis C cohort inclusion criteria, almost 8,000 were known to be alive and not institutionalized and sampled to be surveyed by mail and telephone during 2010–2012 (4).…”
Section: Methodsmentioning
confidence: 99%
“…As reported previously, of more than 12,000 patients who met the hepatitis C cohort inclusion criteria, almost 8,000 were known to be alive and not institutionalized and sampled to be surveyed by mail and telephone during 2010–2012 (4). Up to 8 attempts were initiated in order to complete an interview with each patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…patients with decompensated cirrhosis, renal impairment, HIV/HCV or HBV/HCV co-infections and those who develop recurrent HCV infection following liver transplantation) and pre-treatment assessment of patient's understanding of the goals of therapy as well as the need for adherence and follow up. Studies have shown that reduction in severity of disease and eventual cure for HCV contribute to dramatic reduction in all-cause mortality (including hepatic decompensation events, hepatocellular carcinoma and liver-related mortality) and improve quality of life [61][62][63][64][65][66] . Dhawan documented various drug regimens for the treatment of hepatitis C [67] .…”
Section: Discussionmentioning
confidence: 99%
“…Aunque algunos estudios realizados en Brasil y Estados Unidos han estudiado ampliamente la CVRS en esta población, las diferencias socioculturales no permiten extrapolar estos resultados a nivel local (8)(9)(10)(11)(12).…”
Section: Introductionunclassified